Polymersome Popping by Light‐Induced Osmotic Shock under Temporal, Spatial, and Spectral Control. (16th December 2016) - Peyret, Ariane; Ibarboure, Emmanuel; Tron, Arnaud; Beauté, Louis; Rust, Ruben; Sandre, Olivier; McClenaghan, Nathan D.; Lecommandoux, Sebastien
Abstract: The light‐triggered, programmable rupture of cell‐sized vesicles is described, with particular emphasis on self‐assembled polymersome capsules. The mechanism involves a hypotonic osmotic imbalance created by the accumulation of photogenerated species inside the lumen, which cannot be compensated owing to the low water permeability of the membrane. This simple and versatile mechanism can be adapted to a wealth of hydrosoluble molecules, which are either able to generate reactive oxygen species or undergo photocleavage. Ultimately, in a multi‐compartmentalized and cell‐like system, the possibility to selectively burst polymersomes with high specificity and temporal precision and to consequently deliver small encapsulated vesicles (both polymersomes and liposomes) is demonstrated.